Clinically significant chronic liver disease in people with type 2 diabetes: the Edinburgh Type 2 Diabetes Study - Morling, Joanne R.; Fallowfield, Jonathan A.; Guha, Indra N.; Williamson, Rachel M.; Glancy, Stephen; Strachan, Mark W.J.; Price, Jackie F. (Oxford University Press, 2016)
Background: Type 2 diabetes is an independent risk factor for chronic liver disease, however disease burden estimates and knowledge of prognostic indicators are lacking in community populations.